HUBUNGAN PENGETAHUAN DENGAN SIKAP KELUARGA MERAWAT KLIEN DALAM MENGENDALIKAN HALUSINASI DI UNIT POLIKLINIK JIWA A (UPJA) RSJ. PROF. HB. SA’ANIN PADANG - Dian Rahmi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Healing and relapse in patients with hallucinations or strongly influenced by the roleof family support in caring for the client to control hallucinations. Frequent recurrence impacton clients hallucinations and downs client psychological condition. The purpose of this studyto examine the relationship of knowledge families caring for clients with family attitude incontrolling hallucinations in Unit A Soul Clinic (UPJA) RSJ. Prof. HB. Sa'anin Padang. Thisresearch is a descriptive analytic cross sectional type.The population was 916 with a sampleof 90 families who had taken hallucinogenic clients with accidental sampling. Study used aquestionnaire instrument. Data were analyzed using univariate andbivariate statistical test Chi Square. The results showed 53.3% of respondents had lowknowledge about caring for clients hallucinations, 61.1% of respondents had a negativeattitude in treating clients hallucinations. Results of the bivariate analysis with p value =0.025 shows that there is a significant relationship between the level of knowledge of thefamily with the family in caring for clients attitude hallucinations.Based on these results itcan be concluded that knowledge influence the attitude of the family in caring for clientshallucinations.Keywords: Knowledge, Attitude, Hallucinations.